The Effect of Educational Program on Pain Management, Self-Efficacy Behavior, and Quality of Life among Adult Diabetic Patients with Peripheral Neuropathy Pain: A Randomized Controlled Trial - Abu-Shennar, Jawad Ahmad; Bayraktar, Nurhan (Experimental and Clinical Endocrinology & Diabetes, 2021)
Objective Jordan has a high prevalence of painful diabetic peripheral neuropathy (PDPN), leg complications, and amputations due to diabetes. This study evaluated the effect of educational programs on pain management, self-efficacy behaviors, and quality of life (QoL) among adult patients with PDPN.Methods The randomized controlled trial study was conducted at the Jordanian Ministry of Health hospitals between October 2019 – March 2020. Seventy-two adult patients with PDPN were randomized to an experimental group of 36 patients who attended an educational program and a control group who followed routine diabetic care in the study setting. The data were collected using a socio-demographic and diabetes clinical/laboratory data form, the numeric rating scale (NRS), diabetes self-efficacy scale (DSES), and the quality-of-life questionnaire (EQ-5D). The intervention program consisted of four educational sessions at weekly intervals. Pre-test and post-test evaluations were conducted.Results After the educational intervention, the mean scores of the NRS (p=0.020), DSES (p<0.001), and EQ-5D (p<0.001) in the experimental group improved significantly improved compared to those in the control group. Additionally, while there were no significant correlations between the three study outcomes in the pre-test stage, correlations were observed to be significant after the educational intervention.Conclusion This study shows that the design and implementation of educational intervention combined with routine diabetic care facilitate effective pain management, self-efficacy behaviors, and QoL of patients with PDPN. The health care providers are recommended to use the educational programs for such patients at various levels of services in both health centers and diabetes clinics.
Keywords: painful diabetic peripheral neuropathy; type 2 diabetes mellitus; peripheral neuropathy; self-efficacy behaviors; quality of life